UNSTOPPABLE OBSESSION IN P.J.HOGAN'S CONFESSION OF A SHOPAHOLIC MOVIE (2009): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - MUKTI, NURLITA TRISNA (2011)
The research is focused on the major character, namely Rebecca Bloomwood. The benefit of the study is to give additional information that can be used by the other researchers. The study uses two data sources, namely primary and secondary data source, the primary data source is the movie itself, while the secondary data are taken from some information there are from books and other sources. The method of data collection is qualitative method. The major problem of this study is how unstoppable obsession of the major character reflected in P. J. Hogan's Confession of A Shopaholic Movie. The aim of this study is to analyze P. J. Hogan's Confession of A Shopaholic Movie based on the structural elements and unstoppable obsession of the major character based on the Individual Psychological Approach. The structural elements include character and characterization, setting, plot, point of view, style and theme. Those elements are closely related to each other in order to expose the structural elements of Confession of A Shopaholic. There were six basic concept of individual psychological approach. The analysis is based on the six principle of individual psychology by Alfred Adler that is related to each other and builds a unity that viewed from Rebecca's personality. Thus, most of his principle of life is influenced by inferiority feeling. Based on the analysis, the outcome of this study shows that the major character's obsession leads her to get her dream work (Alette Magazine). She has a big desire in her life; to fulfill it she does many ways. Her ways bring her to become a great woman in the middle of her case. She can do anything to pay her debt. That is called inferiority feeling. The inferiority feeling of Rebecca Bloomwood gives motivation in striving for superiority by using her own way. She shows her life-style in the process of striving life's goal. Finally she can pay all of her debt.